Excellence in sexually transmitted infection (STI) diagnostics: recognition of past successes and strategies for the future - Ronald, A (BMJ Group, 2006)
Diagnostic advances do not generally receive the recognition given to prevention and treatment contributions, for the control and management of infectious diseases including sexually transmitted infections (STIs). In order to identify seminal diagnostic contributions over a half century (1950–2000), the Editorial Board of the WHO Sexually Transmitted Diseases Diagnostics Initiative (SDI) Publication Review or “electronic journal club” were asked to nominate their choices of peer‐reviewed publications for special recognition. From 43 nominations, 13 were voted by a panel of 25 “experts” as having made the most significant contributions. The 1964 article by Thayer and Martin, which identified a selective media for gonococcal culture, was chosen unanimously by all panel members and is identified as the classic STI diagnostic article for this era.